2020
DOI: 10.3390/ijms21072335
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy for Uterine Cervical Cancer Using Checkpoint Inhibitors: Future Directions

Abstract: Immune checkpoint inhibitors (ICIs) have demonstrated marked clinical effects worldwide, and “cancer immunotherapy” has been recognized as a feasible option for cancer treatment. Significant treatment responses have already been attained for malignant melanoma and lung cancer, ahead of gynecologic cancer. In cervical cancer, however, results are only available from phase II trials, not from phase III trials. Cervical cancer is a malignant tumor and is the fourth most common cancer among women worldwide. Since … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(51 citation statements)
references
References 29 publications
0
51
0
Order By: Relevance
“…Besides, accumulating evidence has indicated that tumor-specific mutations could generate neoantigens, thus activating the immunological recognition and killing the tumor cells, indicating that modification of some specific genes could influence the status of TME ( Turajlic et al, 2017 ; Smith et al, 2019 ). In addition, immunotherapy targeting ICPs had achieved tremendous success in multiple human cancers worldwide ( Sun et al, 2020 ), including CC ( Kagabu et al, 2020 ). However, the responses to immunotherapy using ICIs were relatively low in CC patients, and we could not ignore its immune-related adverse reactions ( Frenel et al, 2017 ; Rischin et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Besides, accumulating evidence has indicated that tumor-specific mutations could generate neoantigens, thus activating the immunological recognition and killing the tumor cells, indicating that modification of some specific genes could influence the status of TME ( Turajlic et al, 2017 ; Smith et al, 2019 ). In addition, immunotherapy targeting ICPs had achieved tremendous success in multiple human cancers worldwide ( Sun et al, 2020 ), including CC ( Kagabu et al, 2020 ). However, the responses to immunotherapy using ICIs were relatively low in CC patients, and we could not ignore its immune-related adverse reactions ( Frenel et al, 2017 ; Rischin et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Conventional treatment options for metastatic/recurrent cervical cancer additionally includes radiotherapy and chemotherapy, and this treatment is most often not sufficiently effective for disease management at this late stage. Global reports indicate that in 2018, there were about 569,000 cases of cervical cancer worldwide, with 311,000 deaths [134]; Cancer Fact Sheets: Cervical Cancer. http://gco.iarc.fr/today/data/pdf/factsheets/cancers/cancer-fact-sheets-16.…”
Section: Cervical and Other Female Gynecologic Cancersmentioning
confidence: 99%
“…The distribution of PD-L1 is on the surface of cervical cancer cells, TILs, and APCs, with PD-1 on T cells in the stroma of cervical cancer. The PD-1/PD-L1 axis has been targeted in several clinical trials [25,134], some of which are noteworthy in this report.…”
Section: Cervical and Other Female Gynecologic Cancersmentioning
confidence: 99%
“…In the past five years, the treatment of recurrent and advanced cervical cancer has improved significantly. However, the average overall survival period of advanced cervical cancer is 16.8 months, and the 5-year overall survival rate of all stages is only 68% [3], which has a great impact and harm on patients' living standard and prognosis.…”
Section: Introductionmentioning
confidence: 99%